2020
DOI: 10.1002/ijc.33201
|View full text |Cite
|
Sign up to set email alerts
|

Phase II clinical trial of pazopanib for patients with unresectable or metastatic malignant peripheral nerve sheath tumors

Abstract: Malignant peripheral nerve sheath tumor (MPNST) often does not respond well to chemotherapy and develops against a background of NF1. The purpose of our study was to examine the efficacy of pazopanib against MPNST. Our study was designed as a physician-initiated phase II clinical trial in patients with advanced MPNST. Patients were registered from 11 large hospitals. The primary endpoint was set to clarify the clinical benefit rate (CBR) at 12 weeks according to response evaluation criteria in solid tumors (RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Given the limited adjuvant treatment options, efforts have been made in targeting pathways regulated by the NF1 protein or other associated mutations. Such targets include tyrosine kinase receptor,[ 19 ] epidermal growth factor receptors,[ 1 ] platelet-derived growth factor receptor,[ 5 ] and Ras/Raf signaling,[ 16 ] among others. Inhibition of mTOR signaling has previously been identified as a transiently effective therapy for delaying tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited adjuvant treatment options, efforts have been made in targeting pathways regulated by the NF1 protein or other associated mutations. Such targets include tyrosine kinase receptor,[ 19 ] epidermal growth factor receptors,[ 1 ] platelet-derived growth factor receptor,[ 5 ] and Ras/Raf signaling,[ 16 ] among others. Inhibition of mTOR signaling has previously been identified as a transiently effective therapy for delaying tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Median PFS was 7.4 weeks and median OS 2.5 months [146]. A phase II trial with pazopanib found a 50% clinical benefit rate defined by RECIST in MPNST patients; mOS and mPFS were 5.4 and 10.6 months, respectively [147]. Also, the addition of pazopanib to standard chemotherapy with gemcitabine showed prolonged PFS in STS patients.…”
Section: Targeted Treatment and Clinical Trialsmentioning
confidence: 98%
“…Pexidartinib, a selective c-KIT inhibitor conjugated with colony-stimulating factor 1 receptor, in association with the mTOR inhibitor sirolimus, has been investigated in a phase 1 trial, and reported a long-lasting (>18 weeks) stable disease in three out of six patients with MPNST [ 196 ], thus leading to further investigation in an ongoing phase 2 trial (NCT02584647). Based on the significant VEGF and PDGFR-alpha protein expression in MPNST, the multi-kinase inhibitor pazopanib was evaluated in a phase 2 trial in 12 patients with advanced MPNST, with a clinical benefit rate of 50% at 12 weeks, a PFS of 5.4 months, and an OS of 10.6 months [ 197 ]. Some biological markers, including EGFR, Aurora kinase A (AURKA), or exportin-1 (XPO1), have been demonstrated to be overexpressed in MPNST, thus representing potential druggable pathways.…”
Section: Medical Treatmentsmentioning
confidence: 99%